Using Modified Anthraxin And Its Evaluation For Testing Cell Mediated Immunity And Studying Histopathological Changes In Lab Animals - Al-Jeboury, An' am J.L. (The Iraqi Journal of Veterinary Medicine, 2007)
This study aims to apply a new procedure in preparation of anthraxin fromcell wall extracts of a virulent Bacillus anthracis strain 34F2 (Sterne).Anthraxin was evaluated for potential use as skin testing agent to measurecell-mediated immunity. Guinea pigs were immunized and boostedsubcutaneously with Sterne live veterinary anthrax vaccine. Two weeks afterthe booster dose, animals were skin tested with the antigen which recorded15.6mm as a mean of erythema and 2.5 mm difference of thickness ascompared to the control. Histological changes corresponded with the delayedtype of hypersensitivity (DTH) in which the changes involvedinfiltration of inflammatory cells particularly macrophages, neutrophiles andeosinophils in the skin dermis and in perivascular region in addition toaccumulation of fluid (edema) in the dermis and congestion of blood vessels.